About the problem of author's consciousness ("modes of being", characteristic, typology) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In the article we locally cover the problem of author's consciousness, define a typology of author’s “modus of being”. In the paradigm of Ukrainian Novel Studies of 20-30-ies of XX century we define convergent, divergent and authoritarian types of author’s consciousness as the dominant representative.
Keywords: author’s consciousness; modus; typology; paradigm; communication; novel